Peran Integritas dan Kompetensi SDM dalam Kinerja Sistem Informasi Akuntansi: Studi Moderasi Ancaman Eksternal - Difa Juliandi; Zumratul Meini (LPMP Imperium, 2026)
The aim of the research is to test and analyze the influence of employee integrity, human resource competency on accounting information systems and whether external threats can moderate the relationship between employee integrity and human resource competency on accounting information system performance. The research method is descriptive statistics and verification statistics using the SMART-PLS 4.0 test tool. The research results showed that employee integrity had a significant positive influence on this relationship, human resource competence was proven to have a positive influence on this relationship, external threats were not proven to moderate the relationship between employee integrity and accounting information system performance and external threats were not proven to moderate the relationship between resource competency. human resources and accounting information system performance are not very significant by weakening this relationship.